Financial Feasibility of Cattle Breeding Partnership in South Lampung Regency - Sri Handayani; Irmayani Noer; Eko Win Kenali; Kusuma Adhianto (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2021)
The arising problem in South Lampung Regency is that the pattern of cattle breeding runs on people's businesses scale related to other farming. The farmers established partnerships with feedlots to tackle the hardships of developing cattle breeding for more effective and efficient results. The disproportionate structure of cattle breeding should be analyzed carefully. This research aims to analyze the feasibility of a cattle breeding partnership in the two cattle breeding centers of the South Lampung Regency. The data were quantitatively analyzed with feasibility analysis and the indicators are NPV (Net Present Value), Net B / C (Net Benefit Cost Ratio), PP (Payback Period), and IRR (Internal Rate of Return. The research results indicate that the profit scheme is IDR 20,353,930. As the Net B/C ratio is higher than 1, the business is feasible. Also, the IRR value of 29.9% signifies that the business is economically feasible.